Personalized surgery for the management of pulmonary metastasis - Perentes, Jean Yannis; Zellweger, Matthieu; Gonzalez, Michel (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Since the first report of pulmonary metastasectomy for colorectal cancer (CRC) by Blalock in 1946, many surgical adjustments have been suggested (1). Over the past years, growing evidence has shown that a subset of patients with pulmonary metastases (PMs) may benefit from a curative resection, provided some strict criteria are met (2,3).